EFFECT OF PARTICIPATIVE LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE OF COFFEE TRADING COMPANIES IN KENYA - Rana, Rozy; Ka'ol, Dr. George; Kirubi, Dr. Michael (Journal of Human Resource and Leadership, 2019)
Purpose: The journal aims at assessing the extent to which participative leadership style affects employee performance of coffee trading companies in Kenya. Methodology: The study was guided by the positivism philosophy and used a descriptive correlational research design. The population for the study was 180 senior managers of coffee trading companies in Kenya. Using stratified random sampling technique, a sample size of 139 was determined from the total population and structured questionnaires were administered to collect primary data. Out of 139 questionnaires administered, 117 questionnaires were successfully completed and returned representing a response rate of about eighty four percent (84.2%). Descriptive and inferential statistics were used to analyze the data. The descriptive statistics included means and standard deviations. The inferential statistics included Pearson's correlation coefficients which were used to establish the relationships between variables, one way ANOVA which was used to test the differences between group means and multiple linear regression analysis which was used to test the five hypotheses of the study. The statistical software tool used for data analysis was Statistical Package for Social Sciences (SPSS) Version 20. The results were summarized and presented in tables and in figures. Results: Correlation results showed a positive and significant relationship between participative leadership style and employee performance, r (117) = 0.956, p< .05. Multiple linear regression analysis revealed that participative leadership style significantly predicted employee performance, R2= 0.865, F (1, 115) = 735.111, p < 0.05, Î² = 0.943, p<.05 and therefore the null hypothesis that participative leadership style has no significant effect on employee performance was rejected. Unique contribution to theory, practice and policy: From the study, a contribution to literature on the effect of participative leadership style on employee performance in coffee trading companies in Kenya is made. Suggestion for further studies is made whereby future scholars are recommended that a similar study to be carried out for all supervisory level managers and even lower level managers to assess the effect of participative leadership styles across the spectrum of the organizations